Strategic Approaches to Increasing Refugee Satisfaction at the Makassar Immigration Detention Center - Hasbiadi, Hasbiadi; Hasniaty, Hasniaty; Bakri, Abdul Majid (Jurnal Ilmu Manajemen Profitability, 2025)
This study aims to analyze the strategic approaches implemented at the Immigration Detention Center (Rudenim) in Makassar to enhance service quality for refugees and evaluate their satisfaction with the services provided. Using a descriptive qualitative approach, the research collects data through in-depth interviews with Rudenim leadership, staff, and refugees. The analysis is structured around the SERVQUAL model, which assesses five key service dimensions: reliability, responsiveness, assurance, empathy, and tangibles. The findings indicate that Rudenim Makassar has implemented various strategies to improve service quality, including staff training programs to enhance interpersonal and professional skills, collaboration with international organizations such as IOM and UNHCR to ensure access to essential resources, and enhancements to physical facilities to create a safer and more comfortable environment for refugees. These initiatives have contributed to positive refugee experiences and overall satisfaction. However, challenges remain in certain areas, particularly in responsiveness and the availability of specialized facilities for vulnerable groups, such as children and the elderly. Refugees reported concerns regarding delays in response times and the need for private consultation spaces for sensitive discussions. Despite high overall satisfaction levels, addressing these gaps through targeted improvements will be crucial in ensuring that all refugees receive optimal care and support at Rudenim Makassar.